Analytical Modeling of Channel Potential and Threshold Voltage of Double-Gate Junctionless FETs with a Vertical Gaussian-Like Doping Profile - Singh B.; Gola D.; Singh K.; Goel E.; Kumar S.; Jit S. (My University, 2025)
This paper proposes an analytical 2-D model for the channel potential and threshold voltage of double-gate junctionless FETs with a vertical Gaussian-like doping profile. The 2-D Poisson equation has been solved by using the evanescent-mode analysis to obtain the potential distribution function in the channel. The position of the conduction path also has been modeled to calculate the potential at different positions of the conduction path. The validity of the proposed 2-D potential and threshold voltage models is shown by comparing the results with the simulation data obtained by a 2-D TCAD ATLAS device simulator. © 1963-2012 IEEE.